School Type, Eating Habits, and Screen Time are Associated With Ultra-Processed Food Consumption Among Brazilian Adolescents - Rocha, Luana Lara; Gratão, Lucia Helena Almeida; Carmo, Ariene Silva do; Costa, Aline Bárbara Pereira; Cunha, Cristiane de Freitas; Oliveira, Tatiana Resende Prado Rangel de; Mendes, Larissa Loures (Journal of the Academy of Nutrition and Dietetics, 2021)
The increasing consumption of ultra-processed foods (UPFs) may be a result of the environmental influences to which adolescents are exposed and/or habits acquired since childhood through family interactions. Our aim was to investigate whether type of school administration (public or private), eating habits, and screen time are associated with the percentage caloric contribution of UPFs to total kilocalories consumed by Brazilian adolescents. A cross-sectional secondary analysis of the Study of Cardiovascular Risk in Adolescents (ERICA) performed between March 2013 and December 2014. Overall, 71,553 adolescents from 1,247 public and private schools in 124 Brazilian cities (with a population of more than 100,000) were included. We measured the percentage caloric contribution of UPFs to the total kilocalories consumed, obtained using one 24-hour food recall. Generalized linear models were used, guided by the hierarchical model. Sample complexity was considered using the Stata svy command, with a significance level of 5%. Overall, UPFs contributed an average of 28% (95% CI, 27.80%-28.15%) of total energy intake. Based on the final multivariate analysis, a significantly higher UPF diet was observed among adolescents from private schools (P < .001), those who do not consume meals offered by schools (P < .001), those who do not eat breakfast regularly (P < .05), those who eat in front of screens almost every day or every day (P < .001), and those who spend more time in front of screens (P < .001). The findings of this study indicate that UPF consumption is associated with school type, eating habits, and screen time among Brazilian adolescents.